1999
DOI: 10.1159/000045275
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Glomerular Injury by Kallikrein Infusion in Dahl Salt-Sensitive Rats Is a Bradykinin B<sub>2</sub>-Receptor-Mediated Event

Abstract: Aims: We investigated whether kallikrein infusion attenuates renal injury in Dahl salt-sensitive rats with hypertension and assessed the role of bradykinin-nitric oxide axis in the renal protection using HOE-140, the bradykinin type-2 (B2) receptor specific antagonist. Methods: Subdepressor dose of purified rat urinary kallikrein (RUK) (400 ng/day) was continuously infused through the jugular vein by an osmotic mini-pump for 4 weeks in Dahl salt-sensitive (Dahl S) rats fed a high-salt (2% NaCl) diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…Furthermore, these changes were completely abolished by additional infusion of HOE-140 (33). Taken together with our present findings, these results suggest that activation of bradykinin is critical to prevent and/or buffer glomerular injury caused by salt-sensitive hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, these changes were completely abolished by additional infusion of HOE-140 (33). Taken together with our present findings, these results suggest that activation of bradykinin is critical to prevent and/or buffer glomerular injury caused by salt-sensitive hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…[17][18][19] Similarly, long-term infusion of tissue kallikrein into DSS rats has been shown to attenuate salt-induced renal injury without an apparent effect on blood pressure. 8 These combined data indicate that the tissue kallikrein-kinin system has the ability to exert organ protection independent of its blood pressure-lowering ability. In this study, kinin infusion (500 ng/h) prevented saltinduced renal dysfunction, glomerulosclerosis, tubular damage, and perivascular remodeling in DSS rats.…”
Section: Discussionmentioning
confidence: 97%
“…7,8 The protective effect of the kinin B2 receptor against kidney injury and fibrosis has also been demonstrated in B2 receptor knockout mice. 9,10 However, the in vivo results conflict with studies of kinins in vitro.…”
mentioning
confidence: 99%
“…Moreover, kallikrein infusion increased the urinary excretion of bradykinin and stimulated the excretion of cyclic GMP, suggesting that the KKS-prostaglandin and KKSnitric oxide axes were enhanced by kallikrein infusion [36]. The renal protection observed after kallikrein infusion was an event mediated by B2 receptors since these beneficial effects were completely abolished by concomitant infusion of the kinin B2 receptor antagonist HOE140 [37]. Recent experiments in which the kallikrein gene was delivered into rats with 5/6 reduction in renal mass showed that this experimental maneuver attenuates hypertension and protects Nx rats against renal injury and cardiac remodelling [38].…”
Section: Discussionmentioning
confidence: 97%